The Impacts of Paid Family Leave Benefits: Regression Kink Evidence from California Administrative Data - Sarah Bana; Kelly Bedard; Maya Rossin-Slater (Institute of Labor Economics (IZA), 2018)
Although the United States provides unpaid maternity and family leave to qualifying workers, it is the only OECD country without a national paid leave policy, making wage replacement a pivotal issue under debate. We use ten years of linked administrative data from California together with a regression kink (RK) design to estimate the causal impacts of benefits in the first state-level paid family leave program for women with earnings near the maximum benefit threshold. We find no evidence that a higher weekly benefit amount (WBA) increases leave duration or leads to adverse future labor market outcomes for mothers in this group. In contrast, we document consistent evidence that an increase in the WBA leads to a small increase in the share of quarters worked one to two years after the leave and a sizeable increase in the likelihood of making a future paid family leave claim across a variety of specifications.
Keywords: I18; J13; J16; J18; 330; paid family leave; regression kink design; leave duration; maternal labor supply; temporary disability insurance